Activated Bentonite for Physical, Mechanical, and Durability Properties of Concrete—A Review - Tsion Amsalu Fode; Yusufu Abeid Chande Jande; Thomas Kivevele (Advances in Civil Engineering)
Bentonite mostly exists in many counties and studies reported employment of activated bentonite in the concrete improves concrete performance more than using raw bentonite. However, it is not well-known which range of bentonite activation temperature and employment dose gives the best concrete performance for the sustainability of activated bentonite in construction materials. Therefore, the present study detail reviewed the effect of activated bentonite at different heating temperatures and replacement doses of bentonite on the durability, physical, mechanical, and microstructural properties of concrete. Also, environmental and economic beneficiary of employing activated bentonite in concrete is evaluated. As the review of various studies reveals, activation of bentonite between 201 and 800°C increases the pozzolanic reactivity of bentonite. Hence, the activated pozzolana can easily consume free calcium hydroxide to form a secondary C–S–H gel that can improve the mechanical, microstructural, and durability properties of activated bentonite blended concrete in addition to lessening energy consumption compared to conventional concrete. Besides these, adding 15%–20% of activated bentonite in concrete significantly improves the mechanical properties; specifically, most studies found the optimum activated bentonite dose is 15% by weight of cement in concrete. This replacement indicates lessened energy consumption by around 45% compared to the total employment of ordinary Portland cement in concrete production.